Effect of female sex work-targeted community-based interventions along the HIV treatment cascade in sub-Saharan Africa: a systematic review protocol. Issue 10 (27th October 2020) - Atuhaire, Lydia; Adetokunboh, Olatunji; Shumba, Constance; Nyasulu, Peter S
Abstract : Introduction: Female sex workers (FSWs) are a known high-risk group that are at increased risk of HIV transmission due to exposure to multiple sexual partners and inability to negotiate safe sex attributed to challenging economic circumstances. Previous systematic reviews have examined the effectiveness of HIV interventions prioritising FSWs and have shown that targeted interventions improve access to HIV prevention and treatment services. Interventions that increase FSWs' uptake of services are well documented; however, evidence on specific interventions aimed at improving FSWs' continuity in HIV care along the treatment cascade is lacking. This systematic review aims to document the performance of community-based interventions along the HIV treatment cascade. Methods and analysis: We will use a sensitive search strategy for electronic bibliographic databases, bibliographies of included articles and grey literature sources. In addition, the Joint United Nations Programme on HIV/AIDS and the WHO websites, peer-reviewed conference papers and grey literature sources will be searched for additional reports of sex work programmes. We will include randomised controlled trials, cross-sectional surveys and cohort interventions where community-based HIV services were provided to FSWs and measure the performance of the HIV intervention on one or more cascade stages. We will conduct a systematic review of studies published from 2004 to present within the sub-Saharan Africa region. We will report quantitative study outcomes of HIV testing and diagnosis, linkage to care, initiation on antiretroviral therapy and viral suppression. We will analyse the data using the random-effects meta-analysis method, and funnel plots will be used to assess the publication bias. Ethics and dissemination: This systematic review will not require ethical approval; we will publish data from manuscripts. The results of this study will be disseminated in peer-reviewed journals and conference presentations. PROSPERO registration number: CRD42020157623.